Ageing in Serbia: Perceptions and Experiences of Nursing Home Residents - Lukić, Vesna M.; Stojilković Gnjatović, Jelena N. (Sociološki pregled, 2019)
Population ageing in Serbia has pervading effect on many societal spheres. Paradigm of active ageing highlights the importance for older to lead healthy and productive life. The aim of this paper is to explore active ageing practices of institutionalised older citizens considering their sociodemographic characteristics and migration background. Semi-structured interview, as a qualitative research method was used to grasp perceptions and experiences of 27 older residents in nursing homes regarding adjustment in later life and daily activities. Additional valuable insight on topic was gained from institutional social workers. According to the results, the routine of daily living of the elders varies depending on individual abilities, preferences, health, marital status and migration history. The findings suggest that institutional setting does not have to represent barrier to active ageing, with implications for further research and practice.
Keywords: active ageing; nursing homes; retirement return migration; Belgrade